Improving Children's Early Reading Skills Through Inductive Models of Pictorial Words in Kindergarten - Sitti Marchumah; Silvia Yuni Lestari; Miftakhul Rizki; Fatiha Rosyida (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
Improving children’s early reading skills through pictorial inductive gamest at kindergarten Al-hiro Sidoarjo is the goal to be achieved in this study; this research uses a type of classroom action research; the approach used in this study is qualitative.  The data collection methods used are observation and documentation. The data analysis technique used descriptive analysis from the beginning to the end of the study. With a focus on children's early reading skills, early reading skills are children's ability to recognize letters, read combinations of letters in syllables, and read combinations of syllables into a simple word consisting of two patterned syllables. The letters taught consist of consonants and vowels comprised of a, i, u, e, and o. The teaching of syllables introduced in the k-v-k-v pattern (consonant-vowel-consonant-vowel) is formed from the letters a, b, d, e, i, k, l, m, o, p, s, t, and u. Based on the results of the study, it can be concluded that to improve children's early reading skills through picture word inductive games, the teacher must at least do it based on the standards set. The increase in success can be seen in indicators 1) letter recognition, 2) syllable recognition, and 3) combining syllables into simple words. This increase can be seen in the rise in early reading ability in group B of the action research class at Al Izhar Kindergarten Makassar. This increase can be seen from the average learning outcomes assessment category obtained by children in the first cycle, the average ability is in the starting to develop sort, and the second cycle increases in the developing category as expected (BSH). 15 students are in the nascent category according to expectations. the expectation of the children being observed) the students can enter the excellent type.